Mengeksplorasi Minat Pembelian Ulang Pada Platform E-Commerce - Prisella Putri Octaviyani; Sutianingsih; Fera Valentina; Agustin Diah Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This theoretical review aims to explore the potential influence of free shipping, customer experience, and perceived risk on repurchase intentions in the context of e-commerce. e-commerce has experienced significant growth globally, emphasizing the need to understand the factors that influence consumer repurchase behavior. Based on existing literature, this paper examines the theoretical basis and research results regarding the influence of free shipping interest, customer experience, and risk perception and their potential impact on consumers' willingness to repurchase on e-commerce platforms. This review highlights the importance of the factors free shipping, customer experience and risk perception in shaping consumer behavior and suggests avenues for future empirical research to validate the proposed relationships. Understanding these dynamics can help e-commerce businesses in formulating effective marketing strategies to increase customer retention and loyalty.